Human Papillomavirus Selected Properties and Related Cervical Cancer Prevention Issues - Balmagambetova, Saule; Tinelli, Andrea; Mynbaev, Ospan A.; Koyshybaev, Arip; Urazayev, Olzhas; Kereyeva, Nurgul; Ismagulova, Elnara (Current Pharmaceutical Design, 2020)
High-risk human papillomavirus strains are widely known to be the causative agents responsible for cervical cancer development. Aggregated damage caused by papillomaviruses solely is estimated in at least 5% of all malignancies of the human body and 16% in cancers that affect the female genital area. Enhanced understanding of the complex issue on how the high extent of carcinogenicity is eventually formed due to the infection by the Papoviridae family would contribute to enhancing current prevention strategies not only towards cervical cancer, but also other HPV associated cancers. This review article is aimed at presenting the key points in two directions: the current cervical cancer prevention and related aspects of HPV behavior. Virtually all applied technologies related to HPV diagnostics and screening programs, such as HPV tests, colposcopy-based tests (VIA/VILI), conventional and liquid-based cytology, currently available are presented. Issues of availability, advantages, and drawbacks of the screening programs, as well as vaccination strategies, are also reviewed in the article based on the analyzed sources. The current point of view regarding HPV is discussed with emphasis on the most problematic aspect of the HPV family concerning the observed increasing number of highly carcinogenic types. Present trends in HPV infection diagnostics throughout the human fluids and tissues are also reported, including the latest novelties in this field, such as HPV assay/self-sample device combinations. Besides, a brief outline of the related prevention issues in Kazakhstan, the leading country of Central Asia, is presented. Kazakhstan, as one of the post-soviet middle-income countries, may serve as an example of the current situation in those terrains, concerning the implementation of globally accepted cervical cancer prevention strategies. Along with positive achievements, such as the development of a nationwide screening program, a range of drawbacks is also analyzed and discussed.
Keywords: Kazakhstan